Pengaruh Fermentasi Saccharomyces cerevisiae terhadap Komposisi Kimia dan Cita Rasa Minuman Kopi Penyegar - Ismail Hilmy Muhammad; Darmawan Eman; Ambar Rukmini; Masrukan (BIOFOODTECH : Journal of Bioenergy and Food Technology, 2025)
This study aims to  determine the effect of variations in the concentration of Saccharomyces cerevisiae on the total sugar, alcohol, and caffeine content of refreshing coffee drinks and to determine the level of preference for refreshing coffee drinks produced. This study used a complete random design (RAL) with a single factor, namely the variation in the content  of Saccharomyces cerevisae  (0.1%, 0.3%, 0.6%, 0.9%, and 1.2%) with a fermentation time of 24 hours. Each of the refreshing coffee drinks produced was chemically analyzed (total sugar content, caffeine content, and alcohol content) and organoleptic with hedonic tests including color, aroma and taste. Each treatment was repeated 3 times. The data obtained was carried out Analysis of Variance (ANOVA), if there was a difference between the treatment, a follow-up test was carried out with the Duncan's Multiple Ranges Test (DMRT) Method at the level of 5%. The results of this study show that the concentration  of Saccharomyces cerevisiae  bacteria has an influence on the chemical and sensory characteristics of the refreshing coffee drink produced. The higher the concentration of Saccharomyces cerevisiae used, the lower the total sugar and caffeine content, the alcohol content increases, and the more undesirable the taste, aroma, and color of refreshing coffee drinks. Based on the results of the study, it was shown that  the acceptable refreshing coffee drink was  the maximum treatment of adding Saccharomyces cerevisiae of 0.3 grams, taste (4.3), taste color (4.4), taste aroma (4.4), total sugar content 3.7%, alcohol content 0.2%, and caffeine content 21%.